2014
DOI: 10.1088/0004-637x/783/2/95
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Problems With Using Dark Matter Simulations to Model Stellar Halos

Abstract: The limits of available computing power have forced models for the structure of stellar halos to adopt one or both of the following simplifying assumptions: (1) stellar mass can be "painted" onto dark matter (DM) particles in progenitor satellites; (2) pure DM simulations that do not form a luminous galaxy can be used. We estimate the magnitude of the systematic errors introduced by these assumptions using a controlled set of stellar halo models where we independently vary whether we look at star particles or … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
60
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(61 citation statements)
references
References 39 publications
1
60
0
Order By: Relevance
“…To explore the consequences of such limitations, Bailin et al (2014) compared tagged dark matter particles in hydrodynamical simulations to star particles formed self-consistently in the same simulations. They found moderate disagreement in the distributions of halo stars represented by these two sets of particles, and concluded that tightly bound dark matter is not a reliable proxy for the dynamics of stars in satellite galaxies.…”
Section: Particle Taggingmentioning
confidence: 99%
See 3 more Smart Citations
“…To explore the consequences of such limitations, Bailin et al (2014) compared tagged dark matter particles in hydrodynamical simulations to star particles formed self-consistently in the same simulations. They found moderate disagreement in the distributions of halo stars represented by these two sets of particles, and concluded that tightly bound dark matter is not a reliable proxy for the dynamics of stars in satellite galaxies.…”
Section: Particle Taggingmentioning
confidence: 99%
“…They found moderate disagreement in the distributions of halo stars represented by these two sets of particles, and concluded that tightly bound dark matter is not a reliable proxy for the dynamics of stars in satellite galaxies. However, there is a fundamental difference between the tagging method tested by Bailin et al (2014) and that used by C10. Bailin et al (2014) carried out a single tagging procedure for each satellite at the time of its infall into the main halo, whereas C10 tag each stellar population at the time of its formation.…”
Section: Particle Taggingmentioning
confidence: 99%
See 2 more Smart Citations
“…While this agreement is encouraging, when Helmi et al (2011) repeated the Bell et al (2008) analysis on the Cooper et al (2010) model stellar halos (which were derived by "painting" stars in the "Aquarius" self-consistent dark matter simulations), they found systematically larger deviations from a smooth background than the prior work at a level that was inconsistent with the observations. Recent work by Bailin et al (2014) contrasting simulations with and without Galactic disk components suggest that this inconsistency with both observations and the work might be attributed to the Aquarius simulations lacking the extra potential structure due to the disk.…”
Section: Statistical Comparisons With Observationsmentioning
confidence: 78%